2003
DOI: 10.1111/j.1747-7379.2003.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Young People of Migrant Origin in Sweden

Abstract: This article surveys immigration during the second part of the twentieth century with the aim of determining the origins of the immigrant population and the socioeconomic position of the second generation. It focuses on migration from Turkey from the 1960s onward. Originally, migration from Turkey was within the framework of labor recruitment. These migrants were predominantly ethnic Turks of rural origin. A second wave of migrants from Turkey was composed of Syriani/Assyrians, a Christian minority from easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 2 publications
1
57
0
Order By: Relevance
“…Over the last half century, the proportion of second-generation immigrants in Sweden has risen from being virtually nonexistent to approximately 10 % (Westin 2003;Bengtsson et al 2005). While considerable country of origin and gender variation exists, the schooling experiences of second-generation immigrants are generally poorer than among children of native-born Swedes, on teacher-assigned grades as well as on national and international standardized tests (OECD 2010;Jonsson and Rudolphi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last half century, the proportion of second-generation immigrants in Sweden has risen from being virtually nonexistent to approximately 10 % (Westin 2003;Bengtsson et al 2005). While considerable country of origin and gender variation exists, the schooling experiences of second-generation immigrants are generally poorer than among children of native-born Swedes, on teacher-assigned grades as well as on national and international standardized tests (OECD 2010;Jonsson and Rudolphi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Assyrians/Syrians are a large Christian minority group in Sweden who began immigrating to Sweden in the 1970s because of religious and political persecution [36]. The majority of Assyrians/Syrians in Europe came from Eastern Turkey and sought asylum in Sweden, Germany and France.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that Syriacs represent half of the migrants from Turkey while the remainder is equally divided between ethnic Turks and Kurds. Meanwhile, Westin estimates that migrants from Turkey are divided equally between ethnic Turks, Kurds and Syriacs (Westin 2003). Clearly, there is no certainty about the ethnic distribution of these migrants in Sweden.…”
Section: Migration From Turkey To Swedenmentioning
confidence: 99%